Is long-term particulate matter and nitrogen dioxide air pollution associated with incident monoclonal gammopathy of undetermined significance (MGUS)? An analysis of the Heinz Nixdorf Recall study. (November 2017) - Orban, Ester; Arendt, Marina; Hennig, Frauke; Lucht, Sarah; Eisele, Lewin; Jakobs, Hermann; Dürig, Jan; Hoffmann, Barbara; Jöckel, Karl-Heinz; Moebus, Susanne
Abstract: Background: Exposure to air pollution activates the innate immune system and influences the adaptive immune system in experimental settings. We investigated the association of residential long-term exposure to particulate matter (PM) and NO2 air pollution with monoclonal gammopathy of undetermined significance (MGUS) as a marker of adaptive immune system activation. Methods: We used data from the baseline (2000 − 2003), 5-year (2006–2008) and 10-year (2011–2015) follow-up examinations of the German Heinz Nixdorf Recall cohort study of 4814 participants (45–75 years). Residential exposure to PM size fractions and NO2 was estimated by land-use regression (ESCAPE-LUR, annual mean 2008/2009) and dispersion chemistry transport models (EURAD-CTM, 3-year mean at baseline). We used logistic regression to estimate the effects of air pollutants on incident MGUS, adjusting for age, sex, education, smoking status, physical activity, and BMI. As a non-linear approach, we looked at quartiles (2–4) of the air pollutants in comparison to quartile 1. Results: Of the 3949 participants with complete data, 100 developed MGUS during the 10-year follow-up. In the main model, only PMcoarse was associated with incident MGUS (OR per IQR (1.9 μg/m 3 ): 1.32, 95% CI 1.04–1.67). We further found positive associations between PM size fractions estimated by ESCAPE-LUR and incident MGUS by quartiles of exposure (OR Q4 vs Q1: PM2.5 2.03 (1.08–3.80); PM10 1.97 (1.05–3.67); PMcoarse 1.98 (1.09–3.60)). Conclusions: Our results indicate that an association between long-term exposure to PM and MGUS may exist. Further epidemiologic studies are needed to corroborate this possible link. Highlights: We investigated the impact of exposure to air pollution on incident MGUS. This is the first population based cohort study on this association. Results indicate a possible link between long-term exposure to PM and MGUS. Highlights potential role of PM and different PM fractions for adaptive immunity. Further experimental and epidemiologic studies needed to corroborate our results.